Effects of various recovery modalities on lactate clearance and subsequent exercise performance - O`Connor, R.; Maksimovic, M.; Porcari, J. P.; Schwab, S.; Jaime, S.; Doberstein, S.; Foster, C. (International Journal of Research in Exercise Physiology, 2020)
Introduction: Recovery following exercise plays a vital role in allowing individuals to realize the benefits of exercise training. Clearance of blood lactate (BLa) is considered an important marker of the speed of recovery. Manufacturers of intermittent pneumatic compression (IPC) devices claim that their products help clear BLa more quickly than passive recovery. As such, IPC devices have become increasing popular recovery tool used by athletes. Purpose: The purpose of this study was to compare BLa clearance and subsequent exercise performance following 30 minutes of passive recovery, active recovery, or IPC (NormaTec Pulse 2.0 Recovery System) usage. Methods: Fourteen subjects completed baseline vertical jump, agility, and Wingate testing. On three separate days, separated by a minimum of 72 hours, subjects completed a Tabata workout on a cycle ergometer (8 x 20s @ 125% PPO; 10s recovery). Each Tabata workout was immediately followed by a 30-minute recovery period (i.e., NormaTec, active recovery, or passive recovery), in random order. BLa was measured immediately post exercise and every 5-minutes during each 30-minute recovery condition. Subjects returned to the laboratory 24 hours after each recovery trials to repeat the performance tests. Two recovery questionnaires were also completed to assess subjective recovery. Results: Active recovery and NormaTec resulted in faster BLa clearance during 30 minutes of recovery compared to passive recovery. There was no difference between active recovery and NormaTec during the first 10 minutes post exercise, but thereafter active recovery was superior to NormaTec. There were no significant differences in exercise performance for any of the tests, regardless of the recovery modality. Subjects felt significantly more recovered immediately following the active recovery compared to the passive recovery condition. Conclusion: Active recovery and the NormaTec Pulse 2.0 Recovery System were significantly more effective at clearing BLa than passive recovery during 30-minute recovery sessions. None of the recovery techniques had any significant effect on exercise performance 24-hours later.